2001
DOI: 10.1089/10430340152480276
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Systemic Delivery via a Single Injection of Lentivirus into Human Skin Tissue

Abstract: The skin offers a tissue site accessible for delivery of gene-based therapeutics. To develop the capability for sustained systemic polypeptide delivery via cutaneous gene transfer, we generated and injected pseudotyped HIV-1 lentiviral vectors intradermally at a range of doses into human skin grafted on immune-deficient mice. Unlike Moloney murine leukemia virus (MLV)-based retrovectors, which failed to achieve detectable cutaneous gene transfer by this approach, lentivectors effectively targeted all major cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“…14,15 Several types of viral vectors such as retrovirus, adenovirus, adeno-associated virus (AAV) and lentivirus have been evaluated for epidermal gene transfer in vivo. [16][17][18][19][20][21] Adenovirus vector can efficiently transduce keratinocytes, however, transgene expression is transient owing to the loss of unintegrated vector during epithelium differentiation as well as immunodestruction of target cells. 22 Retroviral vectors based on murine leukemia virus (MuLV) can lead to long-term expression of the transgene in keratinocytes both in in vitro 23 and in vivo, 24 probably owing to integration of the genetic material into the host genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Several types of viral vectors such as retrovirus, adenovirus, adeno-associated virus (AAV) and lentivirus have been evaluated for epidermal gene transfer in vivo. [16][17][18][19][20][21] Adenovirus vector can efficiently transduce keratinocytes, however, transgene expression is transient owing to the loss of unintegrated vector during epithelium differentiation as well as immunodestruction of target cells. 22 Retroviral vectors based on murine leukemia virus (MuLV) can lead to long-term expression of the transgene in keratinocytes both in in vitro 23 and in vivo, 24 probably owing to integration of the genetic material into the host genome.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] It has been reported that a single intradermal injection of VSV-G-pseudotyped HIV-1-based lentivirus into human skin grafted on immunodeficient mice could efficiently transduce most major skin cell types including keratinocytes, fibroblasts, endothelial cells and macrophages within 1 month and persisted for at least 6 months. 20 Pseudotyping lentiviral vector with different envelope proteins has been shown a valuable strategy for optimizing vector tropism to a specific tissue of interest. Up to date, several pseudotyped lentiviral vectors using surface glycoproteins from various viruses were re-targeted or targeted with improved efficiency to different organs or tissues such as liver, lung, muscle and islets.…”
Section: Introductionmentioning
confidence: 99%
“…Khavari and co-workers showed that in vivo lentiviral transduction of the erythropoietin (EPO) gene in various cell types of human skin grafted on immunodeficient mice produced dose-dependent increases in serum EPO and hematocrit. 24 This group has also recently developed a clever strategy in which both gene delivery and lentiviral insertion persistence in skin can be regulated by topical application of the proper ligand/inducer molecules. 25 Regarding corrective approaches, few attempts have been reported.…”
Section: Candidate Diseases For Permanent Keratinocyte Gene Transfermentioning
confidence: 99%
“…Efficient lentiviral transduction of xenografted human skin on immunodeficient mice has been demonstrated previously. 24,25 Furthermore, shRNAs are efficiently produced from lentiviral templates. 23,26 To examine the use of RNAi-based therapeutics in psoriasis skin we selected, in this study, several potentially favourable target sequences within the TNF-α mRNA sequence.…”
Section: Introductionmentioning
confidence: 99%